Body fat mass assessment and obesity classification: a review of the available methods for adiposity estimation - Castelnuovo, Gabriele; de Cuevillas, Begoña; Navas-Carretero, Santiago; Martinez, J Alfredo (Progress in Nutrition, 2021)
Obesity is a growing public health problem, which often leads to severe comorbidities that can reduce quality of life and living expectancy. Overweight is caused by a greater food intake compared to the energy expenditure, which involves an excessive deposition of body fat. The distribution of adipose tissue also varies depending on sex, whereas men usually show android-type obesity, or visceral adiposity, women exhibit more commonly a deposition of fat involving the gynoid gluteo-femoral or subcutaneous type. Overweight and obesity are accompanied by a series of clinical manifestations, being the most common hyperglycemia, hypertriglyceridemia and high blood pressure, which may depend on body fat distribution. Consequently, not only promoting initiatives to adopt a healthy lifestyle based on recommended dietary models and an active living is necessary, but also having reliable techniques for body fat determination. Besides the Body Mass Index (BMI), whose limits on the correct quantification of body fat are known, nowadays diverse approaches for fat measurement are available. In addition, the assessment of body fat could be achieved also through complex methods such as Bioelectric Impedance Analysis (BIA), Dual-Energy X-Ray Absorptiometry (DXA) and Total Body Electrical Conductivity (TOBEC), which may be complemented by approaches to categorize/differentiate obese individuals through classification systems and scores. Indeed, adequate measurement of fat is required for obesity characterization and for management purposes as reported in this review.